Observational cohort study: Getting to the bottom of laryngopharyngeal reflux—It's a motility disorder and not just about the acid. Issue 5 (6th September 2019) - Simpson, Scott B.; Qian, Katherine Y.; Sacks, Raymond; Novakovic, Daniel; Simpson, Rebecca; Van der Wall, Hans
Summary: Background: Laryngopharyngeal reflux (LPR) has been linked with irritable bowel syndrome (IBS). Functional colonic, upper gastrointestinal (GI) and LPR symptoms often coexist and all improve with osmotic laxative therapy. Reflux scintigraphy demonstrates direct contamination of the airway by refluxate. Aims: Evaluate the clinical utility of reflux scintigraphy in managing LPR. Assess the effect of osmotic laxatives combined with acid suppression on both functional GI and LPR symptoms. Methods: Forty consecutive patients referred over 6 months with functional colonic symptoms and significant LPR with a reflux symptom index (RSI)> 13 were followed prospectively. All patients underwent pre‐treatment reflux scintigraphy and gastroscopy with assessment of their reflux finding score (RFS). RSI and RFS were reassessed at ENT follow‐up at a median of 5 months. Functional GI symptoms and RSI were reassessed at a median of 17 months. Results: Thirty‐nine of 40 (97.5%) demonstrated reflux into their oropharynx on reflux scintigraphy. The majority had minimal typical reflux symptoms (55%) and their LPR was refractory to acid suppression alone (62.5%). Short‐term combination therapy reduced both the RSI (22.6‐17.2, P < .01) and RFS (12.3‐7.7, P < .01). Longer term treatment reduced the RSI further (22.6‐9.2, P < .01) correlating strongly with improvement in functional GI symptoms. Conclusions: LPR occurs frequently amongst IBS patients without typical reflux symptoms. Reflux scintigraphy is useful to both diagnose and optimise treatment of LPR. Reducing colonic distension with osmotic laxatives improves both functional GI and LPR symptoms.